PERAN KEPEMIMPINAN KEPALA MADRASAH DALAM MENGEMBANGKAN BUDAYA MUTU - Muhamad Abdul Manan (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2019)
The world is undergoing rapid and global changes. Therefore, in the era of globalization, quality of human resources is needed. The thing that needs to be considered in improving the quality of madrasas is building a quality culture of madrasas. The headmaster of the madrasah provides an important role in the formation of a strong madrasa culture. This study aims to: (1) Obtain a description of the steps of the headmaster of the madrasah in developing the madrasah quality culture, (2) to know the Quality Culture Reality of Madrasah. This research shows that (a) the head of the madrasah articulates the vision and mission for the effectiveness of his leadership in bringing madrasah to become culturally quality continuously. (b) The head of the madrasah has leadership values ​​that are believed, and then realized into the life of the madrasah organization, and has an impact on efforts to improve the quality culture of madrasah. For the process of developing a quality culture through four phases, they are the preparation phase, the acceptance phase, the implementation phase and the commitment phase.